Criminal Reality: An Epistemological Study in Criminal Law - Muslim Jony, Researcher. Ali; Abdel Moneim Abdullah, Prof. Dr. Firas (Basra studies journal, 2024)
The criminal reality and its approach to a partial conception of judicial truth, by confining it to procedural truth, which is the truth of the crime embodied by judicial judgment as a figurative title. The approach to it constitutes a set of procedures stipulated by criminal legislation in the stages of criminal proceedings. Accessing it is not merely a set of procedures in the stages of criminal proceedings; rather, this truth is the evidential truth that results from criminal proof after judicial investigation procedures. What we aim for is that criminal reality is a realistic description of what criminal law should be and what it can accomplish in a specific social context of effective criminal organization that achieves the main function of criminal law. It describes the requirements of criminal treatment of social reality and the accuracy of that treatment, which depends on a high level of logical coherence among the elements of the legal-criminal concept. Thus, it serves as an epistemic intermediary between social reality and criminal law. It is the legitimacy of criminal law and its highest value, which is not realized except through scientific knowledge. This knowledge is only achieved through a scientific approach, represented by the (abstracting approach), legislation, and judiciary. This approach involves removing criminal law from all self-conceptions and overcoming cognitive obstacles that have formed in the mode of thinking of the criminal self, represented by the jurist, legislator, or judge, as a necessary introduction to forming scientific criminal thinking. Finally, judicial truth is a reflection of criminal reality in its legislative dimension, where the conformity is achieved not only between judicial judgment and the reality of the crime, but also when the conformity is achieved between judicial judgment and the function of criminal law.